Management of Common Sexually Transmitted Infections in Primary Health Care: A Systematic Review of WHO and Indonesian Guidelines (2020–2025) - Audra Lovita Vianny; Indah Handayani; Anisa Fitri Amalia (Universitas Ibn Khaldun Bogor, 2026)
Sexually transmitted infections (STIs) remain a major public health issue in primary care, especially in developing countries such as Indonesia. Many general practitioners continue to rely on syndromic management due to limited laboratory facilities, leading to potential underdiagnosis and suboptimal treatment. While the World Health Organization (WHO) emphasizes an etiological and evidence-based approach, Indonesia’s 2023 national guideline still prioritizes syndromic management to match primary care realities. This systematic review, conducted under the PRISMA 2020 framework, compared the WHO (2021) and Indonesian Ministry of Health (2023) guidelines by analyzing 27 eligible publications and official documents. Both share core principles of early detection, effective treatment, partner notification, and prevention counseling. However, significant differences were found in diagnostic methods, antibiotic protocols, and partner management. WHO recommends laboratory-supported diagnosis, while Indonesia maintains syndromic strategies due to infrastructure constraints. To improve STI management, Indonesia should enhance diagnostic capacity, clinician training, and antimicrobial resistance surveillance through collaboration among policymakers, clinicians, and health institutions.